Peran Audit Internal Terhadap Kualitas Pemeriksaan Laporan Keuangan Oleh Audit Eksternal - Mohamad Afrizal Miradji; Putri Ayu Anggelia; Fatimatus Sahro; Adelia Agustin; Ayunny Fiina Ladzatus Shobiroh (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research aims to explore the role of internal audit in influencing the quality of financial statement audits conducted by external auditors. With increasing demands for financial accountability and transparency, the role of internal audit becomes increasingly important in supporting the effectiveness of external audits. However, the relationship and interaction between these two audit functions remain a topic that needs further exploration. Using a mixed-methods approach combining surveys, in-depth interviews, and case studies, this research investigates the perceptions of internal and external auditors regarding the level of collaboration, communication, and coordination between them, as well as their impact on the quality of financial statement audits. The research findings indicate that effective interaction between internal and external audits can enhance audit quality by sharing information, identifying key risk areas, and minimizing duplication of efforts. This research contributes theoretical and practical insights into understanding the important role of internal audit in improving external audit quality, as well as offering recommendations to strengthen the synergy between these two audit functions.